Representasi Kekerasan pada Perempuan dalam Video Klip Tak Mau Berubah-Kesha Ratuliu - M. Andre Ardiansyah; Nani Kurniasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Kesha Ratuliu's video clip “Tak Mau Berubah” shows and depicts violence against women. The purpose of this research is to find out the representations of violence against women that occurs in Kesha Ratuliu's video clip "Tak Mau Berubah". This study uses the theory of Mass Media Social Reality Construction. In this study, the paradigm used is constructivism and the analysis used in this study is the semiotic analysis of Charles Sanders Peirce which has signs, objects, interpretants. The approach in this research is qualitative and the type of research used is descriptive. So that this research produces a representation of physical violence against women such as being thrown by a pillow, then holding the cheek so tightly, being threatened, and humiliated in public.